STRATEGI GURU DALAM PEMBENTUKAN KARAKTER PEDULI LINGKUNGN DI SD NEGERI 22 PALU - Swuanderi, Ketut; Mega Hariani, Ni Made; Sudarsana, Wayan (STAH Dharma Sentana Sulawesi Tengah, 2025)
Caring for the environment is an attitude and action that always tries to prevent damage to the surrounding natural environment and tries to repair damage or health of nature that has occurred. One of the characters that must be developed in schools is environmental concern, environmental concern is an attitude and action that tries to prevent and repair environmental damage. Environmental education must start early so that students become concerned with their environment and have the opportunity to improve their quality of life and learning abilities in the future. The role of teachers in forming environmental care characters is very important and plays an active role in helping students develop a sense of concern for the environment. Teachers can train and accustom students to maintaining environmental cleanliness and preventing environmental damage by carrying out activities that focus on environmental cleanliness, teachers can also be role models for students by practicing environmental concern in everyday life, such as by carrying out environmental cleaning activities or reducing the use of materials that are harmful to the environment. Students' concern for the environment is very necessary in order to create a comfortable atmosphere, so that the teaching and learning process will also run more conducivelyThis study aims to determine the strategies of teachers in the formation of environmentally caring characters as well as supporting and inhibiting factors in the formation of environmentally caring characters at SD Negeri 22 Palu. The method used is qualitative research in the form of descriptive data, using three data collection techniques consisting of: observation, interviews and documentation. The results of the study obtained indicate that the strategies of teachers in the formation of environmentally caring characters are: routine activities, habits, role models, cooperation, spontaneous activities and integration into subjects. Supporting factors for teachers in the formation of environmentally caring characters are: routine activities, the role of teachers, the role of parents, supporting facilities and the Adiwiyata program. On the other hand, the inhibiting factors are: lack of student awareness, socializing outside the school environment and lack of adequate facilities.